2018
DOI: 10.17002/sil..48.201807.277
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mobile-Assisted Language Learning (MALL) on Korean College Students’ English-Listening Performance andEnglish-Listening Anxiety

Abstract: Despite the increasing significance of mobile technology in EFL (English as a Foreign Language) learning, most empirical studies to date have been restricted to vocabulary acquisition, grammar learning, and speaking/writing development. However, the present study focuses its attention on changes in Korean college students' listening performance by making use of diverse mobile applications. In addition, this paper distinctively examines how these students' anxiety levels in English listening may differ after im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These findings of the present study were consistent with those of previous studies that reported that doing listening activities through mobile devices (e.g., smartphones and tablet PCs) (Chinnery, 2006;Evans, 2008;Kim, 2018;Rahimi & Soleymani, 2015), online collaborative learning programs (Magen-Nagar & Shonfeld, 2018), and the flipped classroom method of instruction (Abdolrezapour, 2019;Lai & Hwang, 2016;Qiu & Luo, 2022) had a significant effect on reducing students' FL listening anxiety. A possible explanation for this may be that students' other basic (reading, speaking, and writing) and supportive skills (grammar, vocabulary, and pronunciation) compared to their listening skills improved during the treatment process.…”
Section: Discussionsupporting
confidence: 92%
“…These findings of the present study were consistent with those of previous studies that reported that doing listening activities through mobile devices (e.g., smartphones and tablet PCs) (Chinnery, 2006;Evans, 2008;Kim, 2018;Rahimi & Soleymani, 2015), online collaborative learning programs (Magen-Nagar & Shonfeld, 2018), and the flipped classroom method of instruction (Abdolrezapour, 2019;Lai & Hwang, 2016;Qiu & Luo, 2022) had a significant effect on reducing students' FL listening anxiety. A possible explanation for this may be that students' other basic (reading, speaking, and writing) and supportive skills (grammar, vocabulary, and pronunciation) compared to their listening skills improved during the treatment process.…”
Section: Discussionsupporting
confidence: 92%
“…Listening anxiety has been extensively studied with regard to foreign language learning in an online context: Rahimi and Soleymani (2015) noticed that the use of mobile learning could reduce EFL students' listening anxiety and improve their listening comprehension; Kim (2018) also confirmed that by using mobile phones Korean EFL students had better experience of listening practice. Learning from these studies, one can assume that the technology-supported approach could effectively alleviate 86 students' listening anxiety.…”
Section: Literature Reviewsmentioning
confidence: 87%
“…Ye, Chan and Hsu (2021) highlight in their meta-analysis of teachers' technological pedagogical content knowledge (TPACK) in the context of designing technology-enhanced instruction, that teachers need to work towards eliciting meta-cognitive and reflective thinking within dialogues with students and prompt them to share stories, ideas, experiences and reflections. While some studies advocate for some form of teacher control in MALL contexts (e.g., Kim, 2018), other studies have found that such collaborative learning networks best flourish without direct teacher intervention. Peeters and Pretorious (2020), for instance, found that a teacher's task-based design, with prompts to make students collaborate and share experiences and stories, enhanced 'learner leadership' and fostered the formation of a virtual community of practice.…”
Section: The Role Of Affective Computing Designmentioning
confidence: 99%